Study of the persistence of gunshot residue (gsr) on gloves using colour test - Rafae, Azie Azyanti Mohd (Universiti Sains Malaysia, 2016)
During the discharge of a firearm, gunshot residues (GSR) escape from the openings in the firearm including barrel end, ejection ports, space between the barrel and cartridge holder in revolvers, and deposit on surfaces in the vicinity of discharging firearm. Detection and identification of these GSR particles could provide valuable information in forensic investigations especially for the determination of a shooter. In cases where criminals wearing gloves and GSR were not found on their hands, rapid colour test such as Modified Griess Test (MGT) can be used for an early screening of GSR on the recovered gloves. This research aims to study the persistence of GSR upon different materials of gloves using MGT. During firing test, two different weapons were used, namely Walther*’ P99 semi-auto pistol and .38 revolver, with four different types of gloves worn by the shooters. The results of this study showed that cotton with PVC dotted hand gloves and knitted cotton gloves gave significant results upon MGT with die detection of nitrite compounds. GSRs were more likely to be deposited on die surface of gloves when fired with revolver compared to the semi-auto pistol. These differences between the various weapon types and gloves could be potentially used to clarify the situation at crime scene and should be considered for interpretation of GSR results.